SOUND SYMBOLISM OF FRONT VOWELS IN ENGLISH ONOMATOPOEIC WORDS - Lestari, Indah (Journal of Language and Literature, 2020)
This is a qualitative research that focuses on the meaning represented in the phoneme contained in English onomatopoeic words. Onomatopoeia is word that imitates the sounds of human, animal, things, actions, and nature in the world. Onomatopoeia exists in many reading materials such as comics, fables, tales and poetry. This research focuses on the onomatopoeic words which are contained in Oxford English Dictionary for the dictionary is regularly updated. Out of two kinds of phoneme, which are consonants and vowels, this research limits the investigation for only English front vowels. Based on the manner of articulation, English front vowels are divided into front high tense unrounded vowel /i/, front high lax unrounded vowel /ɪ/, front mid tense unrounded vowel /e/, front mid lax unrounded vowel /ɛ/, and front low lax unrounded vowel /ӕ/. This approach used in this research is called sound symbolism which is a study of relation between sound and meaning. This research applies low-level properties, a mechanism in sound symbolism that is associating the sound to the meaning based on the shared perceptual feature in both phoneme and associated stimuli. The mechanism is used as the method of the research for the researcher explores the characteristics of front vowels contained in English onomatopoeic words that are used to represent the sounds produced by human, animals, natures, machines, and other things. Based on the investigation, the result indicates that the higher vowels the more diminutive meaning it indicates, while the lower vowels the more augmentative meaning it indicates.